2020
DOI: 10.23960/jtep-l.v9i2.122-130
|View full text |Cite
|
Sign up to set email alerts
|

Rancang Bangun Sistem Fertigasi Dengan Menggunakan Venturimeter

Abstract: Di Indonesia banyak petani belum mengenal teknologi-teknologi fertigasi yang akan membantu dan mempermudah pekerjaan para petani-petani di Indonesia. Penelitian ini bertujuan menciptakan alat sistem fertigasi venturimeter, mengetahui debit dari rangkaian sistem, dan debit keluaran nutrisi serta mengetahui debit total dan rasio larutan nutrisi. Penelitian ini dilaksanakan di Laboratorium Daya dan Alat Mesin Pertanian Universitas Lampung pada bulan Juli 2017 sampai Agustus 2017. Rancangan ini menggunakan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The research results of Lanya et al (2020) also reported that the shallow depth of the planting hole can cause the seeds to not be firmly planted because the roots are not deep enough. The heavy load because the seed coat is lifted to the surface of the soil can cause the seeds to fall easily when exposed to water.…”
Section: Planting Depthmentioning
confidence: 99%
“…The research results of Lanya et al (2020) also reported that the shallow depth of the planting hole can cause the seeds to not be firmly planted because the roots are not deep enough. The heavy load because the seed coat is lifted to the surface of the soil can cause the seeds to fall easily when exposed to water.…”
Section: Planting Depthmentioning
confidence: 99%
“…Fertigation is a method of simultaneous fertilizer application with irrigation for cultivated plants (Muharomah et al, 2020;Nabi et al, 2017;Siregar et al, 2018). In this method, fertilization and irrigation are conducted simultaneously to optimize nutrient absorption for the growth of cultivated plants (Lanya et al, 2020;Muli et al, 2021;Pitono, 2019;Rohmah et al, 2018). Irrigation systems with fertigation would be easier and more controlled if applied automatically (Kholilah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pada penelitian sebelumnya telah dilakukan pengujian kinerja sistem kontrol fertigasi dengan metode tetes untuk tanaman bayam yang menunjukkan kinerja yang baik [5]. Sedangkan pada penelitian [6] telah dilakukan perancangan dan pembangunan sistem fertigasi dengan menggunakan venturimeter. Rancangan alat fertigasi menggunakan pipa PVC dan dua venturimeter dipasang paralel, dengan ukuran satu inci.…”
unclassified